Building Social Awareness Through School-Age Youth Guidance (BRUS) for the Young Generation - Nabilaa Faizatuz Zuhriyah (P3M STAI Kuningan, 2024)
Background: The development of social concern among young generations faces serious challenges due to individualism, digital isolation, and declining empathy. These issues necessitate systematic interventions to cultivate prosocial values and behaviors among school-age adolescents.Objective: This research aims to develop and implement the Bimbingan Remaja Usia Sekolah (BRUS) program as a systematic framework for building social concern among school-age adolescents through an integrated guidance approach.Method: The study employed a qualitative design with a phenomenological approach involving 28 adolescent participants aged 13-18 years, 9 program facilitators, and 6 school personnel across six secondary schools. Data collection was conducted through in-depth interviews, focus group discussions, participant observation, and document analysis, then analyzed using a thematic analysis approach.Findings and Implications: Results demonstrated that the 16-week BRUS program successfully enhanced social concern across cognitive, affective, and behavioral dimensions significantly. Participants showed increased frequency in volunteering activities (350%), informal helping behaviors (280%), and social issue advocacy (420%) compared to pre-program baselines. Three-month follow-up data indicated that 75% of participants maintained significantly elevated levels of prosocial engagement. The BRUS program provides theoretical contributions to adolescent character development and offers practical instruments for educators, counselors, and policymakers to integrate social concern development into school-based educational systems.Conclusion: The BRUS program demonstrates effectiveness in cultivating social concern among adolescents, ultimately contributing to developing socially responsible and empathetic young generations.